'Small but mighty': a case study of teacher educators disrupting neoliberal reforms of teacher education and reclaiming a voice in policy conversations. Issue 5 (20th October 2021) - Aydarova, Elena; Rigney, James; Dana, Nancy
ABSTRACT: As attacks on teacher education mount, teacher educators have been urged to take a more active part in policy deliberations. Yet the question of how teacher educators get their voices heard in policy contexts that are not receptive to their expertise remains underinvestigated. This qualitative case study addresses this gap by exploring the work of a group of teacher educators who engaged in advocacy against the introduction of edTPA as a licensure assessment in their state. Through the analysis of interviews, public testimonies, and policy artefacts produced by this group, we documented how over a span of one year the group engaged in policy advocacy that redirected reform efforts from the implementation of edTPA to running a pilot comparing edTPA to another locally produced assessment. The most important outcome of this advocacy, however, was the shift in roles afforded to teacher educators: instead of being seen as objects of reform, they were invited to become participants in policy dialogues about the future of teacher education. The significance of this study lies in offering insights for how teacher educators in other contexts can mobilise their response to neoliberal reforms of teacher education.